Disaster-related physical and mental health: a role for the physician - Kahhar, Md Azizul (Journal of Dhaka Medical College, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15538 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 1-5